2009
DOI: 10.1109/jlt.2009.2021535
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured Fiber Bragg Gratings

Abstract: The first fiber Bragg gratings were accidentally written in a Ge-doped silica fiber using a high power argon-ion laser [Hill 1978]. Following this first evidence of photosensitivity in optical fibers, a huge effort was put into fiber gratings: improving their fabrication (they are now all externally inscribed), obtaining complex profiles, optimizing their performance, and incorporating them into devices and systems. On this line, the last decade was characterized by the birth of an emerging class of fiber grat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 145 publications
0
40
0
Order By: Relevance
“…For instance, FBG incorporated MOF sensors can induce a contra-directional coupling between forward and backward fiber modes through resonant scattering and thus perform very well in strain, pressure and microfluidic refractive index sensing applications [27][28][29][30][31][32]. For instance, C. Martelli et al characterized strain and temperature responses of the FBG on the MOF and showed an increased sensitivity to strain by leaky modes of MOFs which was not presented in conventional fibers [27].…”
Section: Microstructured Optical Fiber Bragg Grating Sensorsmentioning
confidence: 99%
“…For instance, FBG incorporated MOF sensors can induce a contra-directional coupling between forward and backward fiber modes through resonant scattering and thus perform very well in strain, pressure and microfluidic refractive index sensing applications [27][28][29][30][31][32]. For instance, C. Martelli et al characterized strain and temperature responses of the FBG on the MOF and showed an increased sensitivity to strain by leaky modes of MOFs which was not presented in conventional fibers [27].…”
Section: Microstructured Optical Fiber Bragg Grating Sensorsmentioning
confidence: 99%
“…In general, there are two configurations that have been mainly used to design MSF sensors: grating and interferometric-based sensors. In the case of grating-based MSF sensors, Bragg gratings (FBGs) [15] and long-period gratings (LPGs) [16] are inscribed along the MSF; meanwhile, for interferometric geometries, different configurations can be used such as the Mach-Zehnder interferometer [17], Sagnac interferometer (SI) [18], Fabry-PĂ©rot interferometer [19], or Michelson interferometer [20].…”
Section: Introductionmentioning
confidence: 99%
“…The diameter, uniformity and length of the etched fiber can manipulate the intensity of evanescent field, leading to the change of the reflectivity of the grating and thus its SRI sensitivity [6][7][8]. Moreover, FBGs were also directly written in microstructured optical fiber (MOF) without etching the cladding to improve their SRI sensing performance for specific applications, which is based on the intrinsic interaction between the guided mode and medium introduced into the holes of MOF [9,10]. Nevertheless, the devices made in such a way suffer from rather limited detection dynamic range and low sensitivity, especially for some biological or environmental applications which involve aqueous solutions with low level of SRI [5,11].…”
Section: Introductionmentioning
confidence: 99%